Response of Gaussian-modulated guided wave in aluminum: An analytical, numerical, and experimental study - Khan, Sohaib Z.; Khan, Muhammad A.; Tariq, Muhammad; Khan, Kamran Ahmed; Khan, Tariq M.; Ali, Taha (Sage, 2016)
The application of guided-wave ultrasonic testing in structural health monitoring has been widely accepted. Comprehensive experimental works have been performed in the past but their validation with possible analytical and numerical solutions still requires serious efforts. In this paper, behavior and detection of the Gaussian-modulated sinusoidal guided-wave pulse traveling in an aluminum plate are presented. An analytical solution is derived for sensing guided wave at a given distance from the actuator. This solution can predict the primary wave modes separately. Numerical analysis is also carried out in COMSOL® Multiphysics software. An experimental setup comprising piezoelectric transducers is used for the validation. Comparison of experimental results with those obtained from analytical and numerical solutions shows close agreement.
Keywords: Guided wave ultrasonic testing; guided waves; ultrasonic testing; aluminum; numerical simulation; analytical solution; Lamb waves